Assistance for Housewives on Awareness of Eating Fruits and Vegetables through Posters and Leaflets to Increase Knowledge and Attitudes in RT.14 Working Area of Puskesmas Trauma Center Samarinda - Bernadetha; Joko Sapto Pramono; Sri Hazanah (Universitas Muhammadiyah Palu, 2023)
Eating fruits and vegetables is one of the important requirements in fulfilling balanced nutrition. The purpose of this community service activity is to assist counseling in an effort to raise public awareness of eating fruits and vegetables. The targets in community service are housewives in RT 14 Kelurahan Tani Aman, Kader. The service activity began with the socialization of explanations about the awareness of eating fruits and vegetables. The activity was then continued with training on the practice of making fruit and vegetable meals. This service activity program applies implementation methods, namely lectures and discussions, direct practice and evaluation of activities. The lecture and discussion method aims to provide knowledge about awareness of eating fruits and vegetables. Delivery of material using power points and educational videos on awareness of eating fruits and vegetables. Pretest and posttest results for the consumption category: 54% of housewives consume fruits and vegetables well, and 46% of housewives consume vegetables well. The results of this pretest and posttest are still very low. Vegetable consumption is still higher than fruit consumption. Conclusion After this service activity, it is hoped that it can increase awareness and consumption of fruits and vegetables from housewives and can invite people around, especially families, to consume fruits and vegetables.